Chemical studies and biological activities of Goniothalamus Tapis Miq and Goniothalamus Velutinus Airy Shaw - Nabihah, Hamdan (Universiti Malaysia Sarawak, (UNIMAS), 2014)
Chemical studies and biological activities were performed on Goniothalamus tapis Miq and G. velutinus Airy Shaw. Methanolic extracts were partitioned using solvents with increasing polarity to give hexane, dichloromethane, ethyl acetate and methanol partitions. Purification through extensive column chromatography, preparative thin layer chromatography and recrystallization resulted in the isolation and characterization of 5-hydroxy-3-amino-2-aceto- 1,4-napthoquinone and 9-deoxygoniopypyrone from G. tapis, while goniothalamin, aristolactam AII, velutinam and 5,7-dihydroxyflavone were characterized from G. velutinus. Structures of all pure compounds were elucidated based on their spectroscopic data especially mass spectrometry, infrared, nuclear magnetic resonance and comparison with published information. Biological activities screening (antibacterial, antioxidant, brine shrimp toxicity and termiticidal) were performed on all partitions of G. tapis and G. velutinus (bark and root). All G. tapis partitions showed weak antibacterial activities against Bacillus megaterium, Lysteria monocytogenes, Escherichia coli and Salmonella entrica with inhibition zone in the range of 7.2 to 9.7 mm. Ethyl acetate (GTEt) and methanol (GTM) partitions of G. tapis showed strong ability to scavenge DPPH free radicals with EC50 74.5 and 86.0 ppm, respectively and comparable to positive control, butylated hydroxyl toluene with EC50 of 110.1 ppm. 9-Deoxygoniopypyrone, goniothalamin and 5,7-dihydroxyflavone showed weak antioxidant activity with EC50 more than 150.0 ppm. Dichloromethane partitions of G. tapis and G. velutinus barks (GTD and GVBD) exhibited strong toxicity against brine shrimp, Artemia salina with LC50 of 38.2 and 45.1 ppm, respectively and comparable with thymol which was used as positive control with LC50 of 37.5 ppm. Ethyl acetate partition of G. tapis (GTEt) and dichloromethane partition of G. velutinus (GVBD) showed potent termiticidal activity against Coptotermes sp. with 100% mortality at concentration of 10% on the third day of observation. GTEt and GVBD partitions exhibited strongest termiticidal activities with LC50 of 0.04 and 0.06%, respectively.